Experimental Design-Assisted Optimization of Chromatographic Method for the Simultaneous Quantitation of Phenolic Compounds in Dried Flowers Extract - Thorvaldsson , Mira; Mutmainah , Nurul; Briliantama , Asadin; Rahmawati , Sitti; Priyanto, Ashari; Pargiyanti; Setyaningsih, Widiastuti (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2022)
This research aimed to develop and validate a reversed phase-high performance liquid chromatography method to determine phenolic compounds in dried flowers extract simultaneously. The research was divided into two parts: (1) optimization of the separation condition employing a Box Behnken design, and (2) validation test including assessment for the precision, accuracy, and method applicability of a High-Performance Liquid Chromatography (HPLC) coupled with Diode Array Detector (DAD). The studied factors for the optimization of the separation condition were flow rate (0.8−1.2 ml min-1), percentage of the mobile phase at the beginning (0−20% phase B), and end (70−100% phase B) of the gradient program. It was statistically evinced that the chromatographic resolutions (Rs>1.0) indicated acceptable separation for protocatechuic acid, p-hydroxybenzoic acid, protocatechuic aldehyde, vanillic acid, p-coumaric acid, and ferulic acid. A fast separation method (8.00 min) was achieved by applying the optimum condition of a flow rate of 1 mL min-1, mobile phase composition of 20% acidified methanol at the beginning, and 100% acidified methanol at the end of the gradient program. The validation was then performed for the developed method assuring high precision and accuracy. Additionally, the HPLC-DAD method was successfully applied to determine the phenolic compounds in three dried flower extracts revealing that the method was reliable for routine analyses.